King Solomon’s Mines on film: modernity in reverse? - Stephen COAN (E-REA)
There have been four feature films made under the title King Solomon’s Mines, each of them crediting H. Rider Haggard’s Victorian adventure novel published in 1885 as their source. Several films, under different titles, have also claimed either this novel or its sequel Allan Quatermain, as their source material. While close adherence to an original text should not be the criterion for the merits, or otherwise, of a film, it is worth noting that only the first film version of King Solomon’s Mines shot in South Africa in 1918, retained the inter-racial romance found in Haggard’s novel. Later versions substituted an invented white female character as the romantic interest for either the book’s hero, Allan Quatermain, or his fellow adventurer, Sir Henry Curtis. This includes the most recent version released in 2004 starring Patrick Swayze and Alison Doody. That Haggard’s novel (and the first film of his book made thirty-three years later) featured a love story between a white man and a black woman would perhaps seem counterintuitive given the perceived racial mores of the time. Equally, such a love story should seem less problematic given the passage of time. That this is not the case, even in the first decade of the 21st century, this novel presents us with an intriguing example of modernity in reverse. This paper explores the strange trajectory of cinema’s iterations of Haggard’s King Solomon’s Mines.